Favorable Effect of Pemafibrate on Insulin Resistance and β-Cell Function in Subjects with Type 2 Diabetes and Hypertriglyceridemia: A Subanalysis of the PARM-T2D Study - Hiroshi Nomoto; Kenichi Kito; Hiroshi Iesaka; Yuki Oe; Shinichiro Kawata; Kazuhisa Tsuchida; Shingo Yanagiya; Aika Miya; Hiraku Kameda; Kyu Yong Cho; Ichiro Sakuma; Naoki Manda; et al. (MDPI AG, 2023)
Pemafibrate, a novel selective peroxisome proliferator-activated receptor modulator, has beneficial effects on lipid metabolism. However, its effects on glucose metabolism in individuals with type 2 diabetes (T2DM) remain to be fully clarified. This was a subanalysis of the PARM-T2D study, a multicenter prospective observational study on the use of pemafibrate versus conventional therapy for 52 weeks in subjects with T2DM complicated with hypertriglyceridemia. The subanalysis included participants who did not change their treatment for diabetes and did not receive insulin or insulin secretagogues during the study period. Changes in glucose metabolism markers, including homeostatic model assessment (HOMA2) scores and disposition index, were assessed. A total of 279 participants (141 in the pemafibrate group; 138 in the control group) met the criteria for the subanalysis. There were no significant changes in HbA1c during the 52-week study period in both groups. However, the pemafibrate group showed significant improvements versus the control group for insulin resistance assessed by HOMA2-R (−0.15 versus 0.08; estimated treatment difference −0.23 (95% confidence interval −0.44, −0.02); p = 0.03) and maintenance of β-cell function assessed by disposition index (0.015 versus −0.023; estimated treatment difference 0.037 (95% confidence interval 0.005, 0.069); p = 0.02). Correlation analyses showed that improvements in HOMA2-R and disposition index were significantly associated with improvements in lipid abnormalities and γ-glutamyl transpeptidase. In conclusion, pemafibrate reduced insulin resistance and maintained β-cell function in subjects with T2DM and hypertriglyceridemia, presumably by improving lipid profiles and lipid-related hepatocyte stress.